Pour ne pas en finir avec le « genre »... Table ronde - Butler, Judith; Fassin, Éric; Wallach Scott, Joan (Sociétés & Représentations, 2007)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; discipline; genre; histoire; histoire et politique; philosophie; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; thématiques

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

Contract and domination - Pateman, Carole; Mills, Charles W. (Polity, 2007)
« Contract and Domination offers a bold challenge to contemporary contract theory, arguing that it should either be fundamentally rethought or abandoned altogether. Since the publication of John Rawls's A Theory of Justice, contract theory has once again become central to the Western political tradition. But gender justice is neglected and racial justice almost completely ignored. Carole Pateman's and Charles Mills's earlier books, The Sexual Contract (1988) and The Racial Contract (1997), offered devastating critiques of gender and racial domination and the contemporary contract tradition's silence on them. Both books have become classics of revisionist radical democratic political theory. Now Pateman and Mills are collaborating for the first time in an interdisciplinary volume, drawing on their insights from political science and philosophy. They are building on but going beyond their earlier work to bring the sexual and racial contracts together. In Contract and Domination, Pateman and Mills discuss their differences about contract theory and whether it has a useful future; excavate the (white) settler contract that created new civil societies in North America and Australia; argue via a "non-ideal" contract for reparations to black Americans; confront the evasions of contemporary contract theorists; explore the intersections of gender and race and the global sexual-racial contract; and reply to their critics. »--Page 4 de la couverture.
Keywords: approches et analyses; capitalisme; com5170; contrat social; cours; discipline; histoire et politique; intersectionnalité; patriarcat; philosophie; philosophie politique; pol4212; premier cycle; racisme; rapports de domination; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques